Relevance of genetic polymorphism of HLA-B*1502 in carbamazepine-induced cutaneous adverse drug reactions / Hasbullani Zakaria - Zakaria, Hasbullani (2014)
Adverse drug reaction (ADR), commonly termed as unwanted reaction is a longstanding and a major medical problem that comes with many clinically important drugs. ADRs are broadly categorized into predictable (type A) and unpredictable (type B) reactions. Predictable reaction is usually dose dependent, related to the known pharmacologic actions of drugs, and occurs in healthy individuals. Unpredictable reactions are generally dose independent, are not related to the pharmacologic actions of drugs, and only occur in susceptible individuals. Stevens Johnson Syndrome (SJS) and Toxic Epidermal Necrolysis (TEN) are two fatal ADR encountered in some patients prescribed carbamazepine or phenytoin. US FDA had published a medical alert with a recommendation of HLA-B*1502 screening before these two (2) drugs were prescribed to patients with Asian ancestry as the likelihood of SJS/TEN were highly associated with HLA-B*1502. For the methods, eighty (80) healthy unrelated individuals and eighty six (86) patients attending clinics at Department of Neurology of a local hospital were recruited. DNA was extracted from blood samples obtained from each patient. HLA-B*1502 genotype was determined by AS-PCR developed in house. All statistical analysis was performed using SPSS software version 20. P values < 0.05 were considered statistically significant. The strength of association between HLA-B*1502 with CBZ-induced SJS-TEN was estimated by calculating the odd ratio. For the results, among the 86 patients, 40 were newly registered patients and genotype screening was conducted before patients were prescribed with CBZ. Among this group, 17.5% were positive for HLA-B*1502. In another cohort in which CBZ had been withdrawn due to SJS/ TEN; all of them (15) were positive for HLAB* 1502. One patient with positive HLA-B*1502 however did not develop SJS/TEN and is therefore tolerant. The frequency of HLA-B*1502 allele in CBZ-SJS/TEN after CBZ prescribed was 32.6%. The calculated ratio of patients at risk of developing SJS/TEN based on this small samples size is 120.2727 (95% CI: 6.1202 - 2363.5775; p = 0.0016). For the conclusion, the screening of patients for the HLA-B*1502 allele before the initiation of carbamazepine treatment and withholding carbamazepine from HLA-B*1502-positive patients can reduce the incidence of carbamazepine-induced SJS-TEN among the Malaysia. This study conclude that the implementation of HLAB* 1502 screening is necessary to avoid patients at risk of SJS/TEN from being prescribed CBZ due to the high odd ratio observed in this study.